Determination of tizanidine in human plasma by gas chromatography-mass spectrometry - Lee, J; Seo, JH; Kim, DH (ROYAL SOC CHEMISTRY, 2002)
An efficient gas chromatography-mass spectrometry (GC-MS) method was developed and validated for the determination of tizanidine in human plasma. Plasma samples were simply extracted with ethyl acetate at basic pH and the extracts were converted into trimethylsilyl (TMS) derivatives for direct separation by GC-MS with selected ion monitoring (SIM). Reaction of tizanidine with N-methyl-N-( trimethylsilyl) trifluoroacetamide (MSTFA) caused di-trimethylsilylation in the imidazoline moiety and this silylation significantly improved the chromatographic properties of the compound. The determination of tizanidine was accurate and reproducible, with a limit of quantitation of 0.5 ng ml(-1) in plasma. The calibration curve for tizanidine was linear (r(2) = 0.999) over the concentration range 0.5-10.0 ng ml(-1) in human plasma. The intra- and inter-day precision over the concentration range of tizanidine was well within 6.9% (relative standard deviation) and the accuracy was between 99.2 and 110.5%.